Convex lens-induced nanoscale templating - Berard, Daniel J. (National Academy of Sciences, 2014)
We demonstrate a new platform, convex lens-induced nanoscale templating (CLINT), for dynamic manipulation and trapping of single DNA molecules. In the CLINT technique, the curved surface of a convex lens is used to deform a flexible coverslip above a substrate containing embedded nanotopography, creating a nanoscale gap that can be adjusted during an experiment to confine molecules within the embedded nanostructures. Critically, CLINT has the capability of transforming a macroscale flow cell into a nanofluidic device without the need for permanent direct bonding, thus simplifying sample loading, providing greater accessibility of the surface for functionalization, and enabling dynamic manipulation of confinement during device operation. Moreover, as DNA molecules present in the gap are driven into the embedded topography from above, CLINT eliminates the need for the high pressures or electric fields required to load DNA into direct-bonded nanofluidic devices. To demonstrate the versatility of CLINT, we confine DNA to nanogroove and nanopit structures, demonstrating DNA nanochannel-based stretching, denaturation mapping, and partitioning/trapping of single molecules in multiple embedded cavities. In particular, using ionic strengths that are in line with typical biological buffers, we have successfully extended DNA in sub–30-nm nanochannels, achieving high stretching (90%) that is in good agreement with Odijk deflection theory, and we have mapped genomic features using denaturation analysis.